2017
DOI: 10.1016/j.jand.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Mothers’ and Children’s Dietary Intake during Physical and Sedentary Activities: An Ecological Momentary Assessment Study

Abstract: Background Physical activity and diet are major modifiable health behaviors contributing to obesity risk. Although patterns of these behaviors tend to cluster within individuals and within family units, it is unknown to what extent healthy and unhealthy dietary intake might differentially accompany sedentary and physical activities in mothers as compared to their children. Objective Our goal was to examine differences in co-occurrence of activities and dietary intake between mothers and children, as measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…In relation to the within-day intervals for EMA assessments, 35% of the studies established EMA assessments throughout the whole day, whereas 32% scheduled the assessments according to the availability of the participants; for example, studies with children samples avoided school hours (O'Connor et al, 2017). Interestingly, only 26% of studies were to found directly differentiate between working days and non-working days.…”
Section: Profile Of the Populations Studied With Ema And Pamentioning
confidence: 99%
“…In relation to the within-day intervals for EMA assessments, 35% of the studies established EMA assessments throughout the whole day, whereas 32% scheduled the assessments according to the availability of the participants; for example, studies with children samples avoided school hours (O'Connor et al, 2017). Interestingly, only 26% of studies were to found directly differentiate between working days and non-working days.…”
Section: Profile Of the Populations Studied With Ema And Pamentioning
confidence: 99%
“…Therefore, we suggest a duration between 1 and 4 weeks as an optimal balance between habits information and low levels of dropout for future EMA studies. In relation to the within-day intervals for EMA assessments, 35% of the studies established EMA assessments throughout the whole day, whereas 32% scheduled the assessments according to the availability of the participants; for example, studies with children samples avoided school hours (81). Interestingly, only 26% of studies were to found directly differentiate between workingdays and non-working days.…”
Section: Profile Of the Populations Studied With Ema And Pamentioning
confidence: 99%
“…A total of 10 studies described signal-contingent mEMDA methods used in nutritionrelated research [74][75][76][77][78][79][80][81][82][83]. Additional approach details were extracted from multiple related journal articles [79,[84][85][86][87][88][89].…”
Section: Summary Of Signal-contingent Studiesmentioning
confidence: 99%